The forgotten tribe - Joffe, Eddie; Ward, Simon; Whitcher, John.; Wombat Film and Video (Chicago, Ill. Wombat Film & Video, 1990)
Shows John Varty and Lynn Aires experiencing the daily life of African tribesmen in an isolated Zulu village.
VHS.
Credits: Narrator, David Ossman.
Keywords: Africa -- Social life and customs